'When I was transgender': Visibility, subjectivity, and queer aging in Indonesia (Medicine Anthropology Theory, 2017)
This think piece reflects on the ways in which the category ‘transgender’ is used by waria – Indonesia’s ‘national transvestite’ (Boellstorff 2007) – based on ethnographic data collected from informants aged forty years or older in Yogyakarta and Jakarta. I was struck by how this group used the category ‘transgender’ with reference to a particular time in life that stretched from mid-teens to late twenties, a period marked by national and transnational migration for intensive sex work and other labor. Their use of ‘transgender’ to describe certain times of their lives but not others validates scholarly calls to question the privileging of gender and sexuality in analyses of subjectivity. It also troubles the basis of Western assumptions about aging and its relationship to the self, which presumes an experience of time as an orderly chronological progression. Finally, their use of ‘transgender’ demands closer attention to why the use of categories of gender and sexuality might shift across the life course. My informants’ narratives invite us to consider how people in different locations draw upon globalized categories to make meaning. Greater ethnographic attention towards how categories are drawn upon to produce and reflect subjectivity in diverse ways may produce a reflexive understanding of the relationship between categories and the context of entrenched structural inequalities in which they are used.